已知x=√(6-2√5),y=√(3-2√2),求(x+y-2√(xy))/(√x-√y)+(y-x)/(√x+√y)+
2个回答
原式=(√x-√y)²/(√x-√y)+(√y+√x)(√y-√x)/(√x+√y)+xy=(√x-√y)+(√y-√x)+xy=xy=√(6-2√5)√(3-2√2)
主要是化简要灵活
相关问题
已知x^2+y^2-4x+6y+13=0求(xy+y^2/5x^2-5xy+xy+y^2)·(5/x+y)-(y/x-y
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
已知xy=2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)/2y的值.
已知y-x=3xy 求2x+5xy-2y/x-2xy-y
已知y/x-x/y=5,求分式3x^2+xy-3y^2/2x^2-xy-2y^2
已知x=6.61,y=-3.39,求(x-y)(x2+3xy+y2)-5xy(x-y)的值.
已知x/y=2/3求[5y^2/(x-2y)-x-2y]÷(x^2-6xy+9y^2)/(x-2y)的值
已知xy=-2,x-y=3,求(x+y)(x-y)-y平方+(x-y)平方-(6x2y-2xy平方)/2y的值
已知x+y=1/2,求x^2y+xy^2的值 已知x=6,y=1/6,求x^2+xy-5x-5y的值
x/3y=y/2x-5y=6x-15y/x,求(4x^2-5xy+6y^2)/(x^2-2xy+3y^2)的值